Case report: PD-1 inhibitor-based treatment strategies in gastric cancer complicated by bone marrow metastasis and disseminated intravascular coagulation: A report of two cases - Huang, Ren-Ze; Chen, Nuo; Hu, Yan; Hu, Wan-Ming; Wang, Feng-Hua; Chen, Dong-Liang (Frontiers in Oncology, 2023)
1 Abstract Introduction: Gastric cancer (GC) complicated by bone marrow metastasis (BMM) and disseminated intravascular coagulation (DIC) represents poor prognosis and most of these patients would die in a few months. Active treatment strategies such as chemotherapy are effective to restore coagulation function and prolong patients’ survival time. Immunotherapy including programmed death protein 1 (PD-1) or programmed death protein ligand 1 (PD-L1) inhibitors has emerged as a first-line treatment of gastric cancer. However, the efficacy of PD-1 inhibitor-based treatment strategies in these patients remains unknown. Case Description: Herein, we presented two cases of advanced gastric cancer complicated by BMM and DIC, in which two patients received chemotherapy and PD-1 inhibitor as a first-line treatment. Both of them achieved partial response after treatment, and the coagulation function restored. The patient who discontinued the PD-1 inhibitor after 6 months experienced DIC relapse while the other patient who maintains the PD-1 inhibitor treatment cycle remained responsive after 10 months. Conclusions: We speculate that PD-1 inhibitor-based treatment strategies are effective and safe to prolong survival against gastric cancer with BMM and DIC, and the coagulation function is well controlled by the treatment with a combination of immunotherapy and chemotherapy.